Sustainability Analysis of KPBS Pangalengan Milk Processing Business Unit Using Flourishing Business Canvas Method - Syarah Nurul Amaliah; Mukhamad Najib; Siti Jahroh (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Koperasi Peternakan Bandung Selatan (KPBS) as one of the milk cooperatives established Milk Treatment 2 (MT2) as a milk processing business unit to increase the bargaining position of distribution and marketing of milk. The purpose of the research conducted is to analysing the sustainability aspects of MT2 on Flourishing Business Canvas (FBC). The sustainability description of MT2 on FBC makes MT2 able to map sustainability problems that occur in the company. Data and information collection techniques in this study are observation, interviews, and literature study. The study found that Value co-creation conducted by MT2 is the production of high quality and affordable milk-derived dairy products, as well as economic welfare for KPBS members. Other funding showed that the value of co-destruction is due to lack of knowledge, and the weakness of MT2 in markets and capital.Keywords: milk, KPBS Pangalengan, sustainable analysis, sustainable business model, flourishing business canvas